The Development of e-Recipes Mobile Application with Text Recognition: Recipes Collector - YAP, YOKE KEI; Wahid, Noorhaniza (Applied Information Technology And Computer Science, 2024)
e-Recipe is a popular electronic recipe library for single-family kitchens. However, many young adults nowadays prefer collecting recipes online through a screenshot, link saving or notebook marking for their reference. Uncategorized recipes collected can be difficult to find and recording recipes physically will also cause time and space wasting. Therefore, a Recipes Collector mobile application with text recognition technology is developed on the Android platform that allows the user to organize, categorise and record recipes in the cloud. The Prototype Methodology is used to develop this application that including All Recipes, Recipe Collection, Text Recognition (OCR) and Buying List modules. The user acceptance test was conducted among the target user aged 18 to 26 using System Usability Scale (SUS). The results show the application achieved 91.5% in functionality testing and 90.75% in usability testing which is acceptable and excellent as a recipe-collecting application.